The English Village Explained : Britain's Living History. - Yorke, Trevor (Countryside Books, 2014)
Trevor Yorke, with his brilliant illustrations and photographs, describes the historical changes that shaped England's villages. The knowledge they bring you will make each new visit one of rewarding discovery.